Effects of Various Grazing Systems on Grazing and Subsequent Finishing Performance - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2018)
MaxQ tall fescue, a wheat-bermudagrass double-crop system, and a wheat-crabgrass double-crop system have been three of the most promising grazing systems evaluated at the Kansas State University Southeast Agricultural Research Center in the past 20 years, but these systems have never been compared directly in the same study. The objective of this study was to compare grazing and subsequent finishing performance of stocker steers that grazed these three systems.
Keywords: crabgrass; bermudagrass; stocker cattle; grazing; tall fescue; endophyte; wheat